Organizational Resilience in the Hotel Sector: A Systematic Review of Strategies, Practices, and Actions During Crises - HADJ HASSINE, Abir (Revue Internationale des Sciences de Gestion, 2025)
This article conducts a systematic review of the literature on resilience practices, actions, and strategies adopted by hotels during periods of crisis. Building on studies published over the last decade, the review distinguishes between immediate practices, managerial actions, and long-term strategies, and examines how hotels develop resilience through operational adjustments, human resource management, strategic adaptation, and organizational learning. The findings show that resilience in the hotel sector extends beyond short-term responses, reflecting a multidimensional and proactive capability that relies on innovation, knowledge accumulation, and collaboration with internal and external stakeholders. The analysis also reveals significant variations in practices and strategies depending on the type of crisis (health, geopolitical, economic, or environmental) as well as contextual factors such as institutional environments, cultural norms, and resource availability. These factors are particularly influential in emerging economies, where resilience mechanisms often rely on flexibility, social capital, and inter-organizational cooperation. This article contributes to the literature by linking hotel resilience to dynamic capabilities and strategic renewal and provides practical insights for hotel managers seeking to strengthen organizational adaptability and long-term competitiveness.